Karakteristik Anatomi Akar dan Batang Tanaman Jeruk Batang Bawah sebagai Parameter Penduga Vigor Tanaman Jeruk Keprok Rimau Gerga Lebong (RGL) - Yulianti, Farida; Latif Adiredjo, Afifuddin; Soetopo, Lita; Ashari, Sumeru (Jurnal Hortikultura Indonesia, 2020)
The citrus plant’s vigor was affected by rootstock used. This study aims to obtain a correlation between the root and stem anatomical characters of citrus rootstock and to obtain predictor variables of RGL mandarin citrus vigor. The research was conducted at Tlekung Field Trial of ICISFRI from June 2019 to March 2020. The experiment used JC, Citrumelo and Kanci rootstocks with RGL mandarin as a scion. The experiment was carried out in a randomized block design with five replications. The results showed that the growth of JC and Citrumelo were the same, and higher than that of Kanci. The three types of rootstocks had different anatomical characters. The correlation analysis showed that characteristics of percentage and vessel area of xylem both at the roots and stems were positively correlated with rootstock plant height. The Kanci rootstock had the smallest percentage and vessel area of xylem. The JC had rootstock the highest percentage of xylem and vessel area of xylem both at the roots and the stems. The Citrumelo rootstock has the highest density of xylem / mm2 vessels. Citrumelo rootstock had the percentage of xylem, while JC rootstock has the largest vessel size of xylem. Evaluation results on three-year old RGL mandarins showed that JC and Citrumelo rootstocks caused higher plant height and canopy volume than Kanci one. The characters of percentage and vessel area of xylem can be used as a predictor of RGL mandarin citrus vigor. Keywords: citrus rootstock, RGL mandarin citrus, anatomical characters, xylem, vigor